Developing blackboard systems for product design using a graph decomposition algorithm - Wu, Tao. (2008)
In this project, the relationship between graph decomposition and the resultant blackboard system is further studied. To avoid the burden of decomposing a complex graph manually, an application program implementing the algorithm named “GraphDec” is developed. An illustration of 35 hypothetical skeleton blackboard systems that comprise different knowledge organizations is provided.